I don’t know how ybyybbyyb
Answer:
C. x = 3, y = 2
Step-by-step explanation:
If both triangles are congruent by the HL Theorem, then their hypotenuse and a corresponding leg would be equal to each other.
Thus:
x + 3 = 3y (eqn. 1) => equal hypotenuse
Also,
x = y + 1 (eqn. 2) => equal legs
✔️Substitute x = y + 1 into eqn. 1 to find y.
x + 3 = 3y (eqn. 1)
(y + 1) + 3 = 3y
y + 1 + 3 = 3y
y + 4 = 3y
y + 4 - y = 3y - y
4 = 2y
Divide both sides by 2
4/2 = 2y/2
2 = y
y = 2
✔️ Substitute y = 2 into eqn. 2 to find x.
x = y + 1 (eqn. 2)
x = 2 + 1
x = 3
OK so there is 72% of the company left to share. Divide that by six you get 12.
Each shareholder has 12% of the company.
Answer:
13
Step-by-step explanation:
it is very easy
19-6=-11
it is false
now the true equation is
19-6= 13
Answer:
(-3,-10)
Step-by-step explanation:
Given part a, you seem to know the midpoint formula. We can easily edit that to figure out what an endpoint is. Say that a variable "a" represents the x coordinate of D, and b the y coordinate. As the x coordinate of M is 0.5, and the x coordinate of C is 2, we can use the midpoint formula to say that
. Multiplying both side by 2, we get that a+2=-1, and subtracting both sides by 2, a=-3. Similarly,
, b+7=-3, and b=-10, making our answer (-3, -10). Let me know if you have any questions.